Canine Choroid Plexus Tumor with Intracranial Dissemination Presenting as Multiple Cystic Lesions - Trisha J. Oura; Peter J. Early; Samuel H. Jennings; Melissa J. Lewis; Jeremy R. Tobias; Donald E. Thrall (Case Reports in Veterinary Medicine)
A Miniature Pinscher developed acute blindness and behavioral changes. On magnetic resonance imaging (MRI), there were multiple small intra-axial cystic lesions, and primary differential diagnoses included primary or metastatic neoplasia and neurocysticercosis. These cystic lesions were subsequently diagnosed histopathologically as disseminated choroid plexus carcinoma. This is only the second documented description of this diagnosis in a dog, but both patients had very similar MRI findings. This patient adds to the literature about the MRI characteristics of choroid plexus tumors and indicates that choroid plexus tumor should be considered as a possible cause of small multifocal intra-axial cystic brain lesions in dogs, regardless of whether a primary intraventricular lesion is visible.